All My Friends Are Doing It: Potentially Offensive Sexual Behavior Perpetration Within Adolescent Social Networks. (13th June 2014) - Jewell, Jennifer; Spears Brown, Christia; Perry, Brea
<x xml:space="preserve">Abstract</x> The current study used social network analysis to investigate peer network and individual predictors of potentially offensive sexual behaviors among high school students. Ninth‐grade students (n = 308; 158 girls) completed surveys assessing their perpetration of potentially offensive sexual behaviors against their peers, as well as measures of their sexualized gender stereotypes and propensity to self‐monitor. Participants selected up to eight of their closest friends from a roster. Results revealed homophily of potentially offensive sexual behaviors, such that adolescents perpetrated similar amounts of physical/verbal, electronic, and homophobic behaviors as their friends. Characteristics of the peer network (e.g., mean network perpetration, centrality of individual, and gender composition) and the individual adolescent (e.g., gender, sexualized gender stereotypes, self‐monitoring) predicted adolescents' own behavior.